Beyond CCT: The spectral index system as a tool for the objective, quantitative characterization of lamps. (February 2018) - Galadí-Enríquez, D.
Highlights: A simple system for a physically meaningful, quantitative characterization of lamp spectra. Spectral indices are straightforward to compute from the standard spectra currently obtained at any lab. A natural link between lighting engineering and astrophysics, relevant for the study of artificial light at night. A system potentially useful for industrial certification, legal regulation and biophysical studies. Abstract: Correlated color temperature (CCT) is a semi-quantitative system that roughly describes the spectra of lamps. This parameter gives the temperature (measured in kelvins) of the black body that would show the hue more similar to that of the light emitted by the lamp. Modern lamps for indoor and outdoor lighting display many spectral energy distributions, most of them extremely different to those of black bodies, what makes CCT to be far from a perfect descriptor from the physical point of view. The spectral index system presented in this work provides an accurate, objective, quantitative procedure to characterize the spectral properties of lamps, with just a few numbers. The system is an adaptation to lighting technology of the classical procedures of multi-band astronomical photometry with wide and intermediate-band filters. We describe the basic concepts and we apply the system to a representative set of lamps of many kinds. The results lead to interesting, sometimes surprising conclusions. The spectral index system is extremely easy to implement from the spectral data that are routinely measured at laboratories. Thus, including this kind of computations in the standard protocols for the certification of lamps will be really straightforward, and will enrich the technical description of lighting devices.